Isolation of Phenolic Compounds From Eco-Friendly White Bee Propolis: Antioxidant, Wound-Healing, and Anti-Alzheimer Effects - Necip, Adem; Demirtas, Ibrahim; Tayhan, Secil Erden; Isik, Mesut; Bilgin, Sema; Turan, Ismail Furkan; Beydemir, Sukru (Wiley, 2024)
This study presents the first findings regarding extraction, isolation, enzyme inhibition, and antioxidant activity. The oral mucosal wound-healing process was investigated using propolis water extract (PWE) incubation with gingival fibroblast cells and concluded that propolis was effective on the oral mucosal wound-healing pattern compared to untreated controls. Additionally, phenolic compounds (fraxetin, apigenin, galangin, pinobanksin, chrysin, etc.) were isolated from propolis, and their chemical structures were elucidated using comprehensive spectroscopic methods. The antioxidant and anti-Alzheimer potential activities of PWE and some isolated compounds were screened and revealing their inhibitory effects on acetylcholinesterase (AChE) with IC50 values ranging from 0.45 +/- 0.01 to 1.15 +/- 0.03 mM, as well as remarkable free-radical scavenging and metal reduction capacities. The results suggest that these compounds and PWE can be used as therapeutic agents due to their antioxidant properties and inhibitory potential on AChE. It can also be used for therapeutic purposes since its wound-healing effect is promising.
Isik, Mesut/0000-0002-4677-8104; Bilgin, Sema/0000-0001-5921-5434; Demirtas, Ibrahim/0000-0001-8946-647X; Erden Tayhan, Secil/0000-0001-8473-5896; Neci̇p, Adem/0000-0002-2092-7829
Keywords: Anti-Alzheimer; Antioxidant Capacity; Isolation of Phenolics; Phytochemical; Propolis; Wound-Healing